Chromomycin A5 induces bona fide immunogenic cell death in melanoma - Florêncio, Katharine Gurgel Dias; Edson, Evelline Araújo; Fernandes, Keilla Santana da Silva; Luiz, João Paulo Mesquita; Pinto, Francisco das Chagas Lima; Pessoa, Otília Deusdênia Loiola; Cunha, Fernando de Queiroz; Machado-Neto, João Agostinho; Wilke, Diego Veras (Frontiers in Immunology, 2022)
Purpose Some first-line cytotoxic chemotherapics, e.g. doxorubicin, paclitaxel and oxaliplatin, induce activation of the immune system through immunogenic cell death (ICD). Tumor cells undergoing ICD function as a vaccine, releasing damage-associated molecular patterns (DAMPs), which act as adjuvants, and neoantigens of the tumor are recognized as antigens. ICD induction is rare, however it yields better and long-lasting antitumor responses to chemotherapy. Advanced metastatic melanoma (AMM) is incurable for more than half of patients. The discovery of ICD inducers against AMM is an interesting drug discovery strategy with high translational potential. Here we evaluated ICD induction of four highly cytotoxic chromomycins A (CA5-8). Methods ICD features and DAMPs were evaluated using several in vitro techniques with metastatic melanoma cell line (B16-F10) exposed to chromomcins A5-8 such as flow cytometry, western blot, RT-PCR and luminescence. Additionally an in vivo vaccination assay with a syngeneic murine model (C57Bl/6) was performed to confirm ICD induction. Results B16-F10, a metastatic melanoma cell line, treated with CA5-8 and doxorubicin exhibited ICD features such as autophagy and apoptosis, externalization of calreticulin, and releasing of HMGB1. However, CA5-treated cells had the best profile, also inducing ATP release, ERp57 externalization, phosphorylation of eIF2⍺ and altering expression of transcription of genes related to autophagy, endoplasmic reticulum stress, and apoptosis. Bona fide ICD induction by CA5 was confirmed by a C57BL/6 mice vaccination assay with CA5-treated cells. Conclusion CA5 induces bona fide immunogenic cell death on AMM.